Note on a Meeting Held at the United Nations to Discuss DPI Cooperation for Relief to the Hungarian People - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly An appeal to governments was launched asking them to make contributions to relief for Hungary in pursuance of General Assembly Resolution A/RES/393.